Unraveling gender dynamics in the impact of work-family conflict on alcohol consumption among Australian parents. - Maciejewski, Linda; Tuppat, Julia (My University, 2025)
This study examines the relationship between work-to-family conflict (WTFC) and family-to-work conflict (FTWC) and drinking frequency and quantity by gender. Using longitudinal data from the Household, Income, and Labour Dynamics in Australia (HILDA) survey and analyzing around 40,000 observations of employed parents, we employ Tension Reduction Theory, Affect Regulation Theory, and Conservation of Resources Theory to propose an increase or decrease in alcohol consumption. Further, we expect gender differences due to gender roles and drinking motives. The results of our ordered logit regression models with fixed effects show that an increase in WTFC is positively and significantly associated with an increase in drinking frequency. However, this effect is only found among mothers but not fathers. In contrast, while there is no significant association with drinking quantity overall, gender differences are observed: higher levels of FTWC are significantly associated with an increase in drinking quantity, but only among fathers and not mothers. These findings highlight the importance of further research on conflict directions, the role of coping motives, and gender-specific responses to work-family conflict concerning alcohol consumption.
Community, Work & Family
Keywords: Gender; Health and wellbeing